2016
DOI: 10.2147/dddt.s114962
|View full text |Cite
|
Sign up to set email alerts
|

Smart nanocrystals of artemether: fabrication, characterization, and comparative in vitro and in vivo antimalarial evaluation

Abstract: Artemether (ARTM) is a very effective antimalarial drug with poor solubility and consequently low bioavailability. Smart nanocrystals of ARTM with particle size of 161±1.5 nm and polydispersity index of 0.172±0.01 were produced in <1 hour using a wet milling technology, Dena® DM-100. The crystallinity of the processed ARTM was confirmed using differential scanning calorimetry and powder X-ray diffraction. The saturation solubility of the ARTM nanocrystals was substantially increased to 900 µg/mL compared to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 63 publications
1
29
0
Order By: Relevance
“…Therefore, it is imperative to address the issue of poor water solubility of BCSII drugs; herein, for silibinin, bioavailability is subsequently substantially enhanced. The dissolution studies showed effectively enhanced dissolution rate of the poorly water-soluble silibinin, which is indicative of improved bioavailability 45. Additionally, Prandtl and Noyes–Whitney developed an equation, wherein the relationship among the particle size, hydrodynamic boundary layer, velocity of the surrounding liquid, surface area, and dissolution rate has been expressed, showing that greater surface area and smaller thickness of the diffusion layer can increase the dissolution rate of the particles 46.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, it is imperative to address the issue of poor water solubility of BCSII drugs; herein, for silibinin, bioavailability is subsequently substantially enhanced. The dissolution studies showed effectively enhanced dissolution rate of the poorly water-soluble silibinin, which is indicative of improved bioavailability 45. Additionally, Prandtl and Noyes–Whitney developed an equation, wherein the relationship among the particle size, hydrodynamic boundary layer, velocity of the surrounding liquid, surface area, and dissolution rate has been expressed, showing that greater surface area and smaller thickness of the diffusion layer can increase the dissolution rate of the particles 46.…”
Section: Discussionmentioning
confidence: 97%
“…The cumulative dissolution of ITZ-PBLA-Nanos was up to 89% within 2 min, similar to that of the Sporanox ® injection which is 91% within 2 min. However, the dissolution was much slower for the crude ITZ suspensions and only 27% was dissolved within 2 h. The enhanced dissolution of the nanosuspension was due to the markedly enlarged total surface area and enhanced saturation solubility of ITZ associated with smaller particle size of the nanoparticles compared with that of the crude suspensions (Kassem et al, 2016;Li et al, 2016;Shah et al, 2016;Xu et al, 2016;Yang et al, 2014). While the dissolution profile of the ITZ-PBA-Nanos was essentially the same as Sporanox ® injection, the toxicity of the nanosuspension was greatly reduced because of the better biocompatibility of PEG-PBLA than that of cyclodextrin in Sporanox ® injection (see the acute toxicity section below).…”
Section: In Vitro Dissolutionmentioning
confidence: 99%
“…Nanosuspensions are colloidal dispersions stabilized by various electrostatic or steric stabilizers where the particles are in the range of sub-microns (Pu et al, 2009b). Nanosuspensions are considered to be a suitable alternative in the formulation of BCS class-II drugs with low solubility due to their high dissolution velocity and high loading capacity (Kassem et al, 2016;Liu et al, 2016;Shah et al, 2016). Although there are various advantages of using nanosuspensions for the delivery of BCS II drugs, poor physical stability has been a key drawback .…”
Section: Introductionmentioning
confidence: 99%
“…The zeta potential value obtained was −22.1±2.2 mV, and the literature reported value for nanosuspensions is ±20 mV 29,30. The chemical stability of the produced nanosuspensions was evaluated for 1 week as per the method reported previously 20. The % of the drug content of dexibuprofen nanosuspension stored for 7 days was 96.9%±2.6%.…”
Section: Resultsmentioning
confidence: 75%